Identifikasi Faktor Risiko Perforasi Gaster Pada Pasien Usia 18-33 Tahun di Rumah Sakit Umum Daerah Kabupaten Sumbawa Periode Tahun 2020 - Lalu Fahril Ilham; Lalu Fauzan Adi Yuliansyah (Lombok Medical Journal, 2025)
Gastric perforation is the leakage of stomach acid into the abdominal cavity which will cause peritonitis and is an emergency. The risk of mortality due to the disease is 10 times greater than other acute abdominal diseases. One of the efforts to prevent gastric perforation is to know the risk factors that can increase the possibility of this disease. This study uses a retrospective descriptive method. Samples were taken using the total sampling technique. The data used are secondary data using medical record data from patients diagnosed with gastric perforation with an age range of 18-33 years in the 2020 period at the Sumbawa Regency Regional General Hospital. A total of 13 people suffered from gastric perforation at the age of 18-33 years with an average age of respondents of 23 years. All respondents were of different genders (100%). A total of 12 people (92.3%) had a smoking habit and 8 people (61.5%) consumed alcohol. There was 1 person (7.6%) with a history of Gastroesophageal Reflux Disease (GERD) and 5 people (38.4%) suffered from peptic ulcers disease. 15.4% of respondents had a history of consuming Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and 92.3% with a history of consuming traditional herbal medicine containing Curcumae rhizoma, Zingiberis rhizoma, Zingeberis aromaticae, and caffeine. In this study, all respondents were male and the average age was 23 years in the age range of 18-33 years. Risk factors found in respondents were smoking habits, alcohol consumption, history of Gastroesophageal Reflux Disease (GERD) and peptic ulcers disease, consumption of NSAIDs and traditional herbal medicine containing Curcumae rhizoma, Zingiberis rhizoma, Zingeberis aromaticae, and caffeine which have relaxing side effects and become addictive after consuming them.